Formulation of Distributed Optimal Power Flow Control Using Partitioning Strategy - Deokate, Manoj Bhaurao; Surjuse, Rajesh S. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The main objective and purpose of the present study is to demonstrate the formulation of OPF (Optimal Power Flow) distribution using a partitioning system and to determine the generation cost. OPF is one of the significant issues in analyzing the energy system. Thus, to resolve the OPF problem with power networks deal with system size problems and streaming processing methods. In a distributed partitioning system, the whole system independently tries to resolve a minor problem based on the limited inputs according to their areas. In a distributed system, the entire standard IEEE bus system should be divided into sub-sections in two areas. Processors should be capable of resolving minor issues related to partitions by allocating space properly. The case study of the IEEE-14 Bus system is being tested and the findings obtained are exhibited.